ANALISIS FAKTOR KEMENANGAN ANNAJ MUST TSAQIB DALAM PEMILIHAN KEPALA DESA PAHESAN KECAMATAN GODONG KABUPATEN GROBOGAN - Khoirur Rohman; Kushandayani .; Fitriyah . (Journal of Politic and Government Studies, 2016)
ABSTRACT Village is a reflection of a country, because village is the smallest part of government in a country. The village government consists of the village head and village as an element of village administration. Village heads elections conducted by the election committee conducted through several stages, netting and screening of candidates, the establishment candidate, campaign, vote, and the determination of the elected candidates. Village Head Election in Pahesan Village, Godong Subdistrict, Grobogan District, followed by several candidates and eventually won by Annaj muts Tsaqib. This research uses descriptive method and aims to provide an overview of the factors of Annaj muts Tsaqib’s victory as village heads of Pahesan. This research was conducted in the village Pahesan Godong Subdistrict Grobogan. The research approach used in this study is a qualitative approach. Factors of Annaj muts Tsaqib’s victory in the village elections is through the approach to the villagers by visiting homes and public places, using a strategy of pre-dawn raid, donated material and non-material to the villagers and the perception of the villagers that its competitors, namely Qomarudin, deemed not able to lead the country if elected. Key Words: The village heads elections, Factors victory